Soybean seeds quality under different levels of vigor and fertilizing supplying (Research, Society and Development, 2020)
The aims to evaluate the soybean seeds quality in response to the vigor level of seeds and the fertilizing distribution system in the sowing row. The experimental design was random blocks organized in factorial scheme, being two growing environments (Passo Fundo – RS and Ernestina – RS) x three vigor levels classified as high, medium and low (90%, 70% and 60% vigor, respectively) x three fertilizing distribution systems (no distribution, conventional and overflow), and the treats disposed in four replicates. The measured characters were thousand seeds mass, germination, accelerated aging, electric conductivity, viability and vigor, shoot and root length, shoot and root dry matter and field emergency. Vigor and physiologic quality of produced seeds are intimately related to characteristic of environment of production and vigor level of used seeds. Elevated physiologic potential are obtained in seeds produced in specifically using seeds with high vigor independent of the fertilizer distribution system.